Die Repräsentation der Habsburg-Lothringischen Dynastie in Musik, visuellen Medien und Architektur, ca. 1618-1918 - Telesko, Werner (2017)
This volume consists of conference papers from the Vienna conference about Habsburg representation which took place in June 2015. The theme is the different forms of representation of the Habsburg-Lorraine dynasty in art and music from the 17th to the early 20th centuries. The many forms of representation employed are discussed in four sections, dealing with the themes and media used, with the relationship between ruler, state and nation, with the networks of the actors involved and with the relationship between ceremonial spaces and the diverse 'publics' being addressed.